Fracture Toughness Assessment of Pipeline Steels Under Hydrogen Exposure for Blended Gas Applications - Hesamedin Ghadiani; Zoheir Farhat; Tahrim Alam; Md. Aminul Islam (Metals)
Hydrogen embrittlement (HE) is a critical concern for pipeline steels, particularly as the energy sector explores the feasibility of blending hydrogen with natural gas to reduce carbon emissions. Various mechanical testing methods assess HE, with fracture toughness testing offering a quantitative measure of defect impacts on structural safety, particularly for cracks arising during manufacturing, fabrication, or in-service conditions. This study focuses on assessing the fracture toughness of two pipeline steels from an existing natural gas network under varying hydrogen concentrations using double cantilever beam (DCB) fracture tests. A vintage API X52 steel with a ferritic–pearlitic microstructure and a modern API X65 steel with polygonal ferrite and elongated pearlite colonies were selected to represent old and new pipeline materials. Electrochemical hydrogen charging was employed to simulate hydrogen exposure, with the charging parameters derived from hydrogen permeation tests. The results highlight the differing impacts of hydrogen on the fracture toughness and crack growth in vintage and modern pipeline steels. These findings are essential for ensuring the safety and integrity of pipelines carrying hydrogen–natural gas blends.